Imaging single molecules by optical absorption at room temperature - Celebrano, M; Kukura, P; Renn, A; Sandoghdar, V (2011)
Since its first development and applications in the early 1990s, single molecule detection has become a powerful tool for a wide range of studies, ranging from biophysics to quantum optics. However, this approach has been limited so far to species with high fluorescence quantum yield. Over the past few years, we have developed extinction detection and spectroscopy as an alternative to fluorescence for investigating single nano-objects such as metallic nanoparticles, viruses, dye molecules, and quantum dots [1-5]. The contrast mechanism at work relies on the coherent interference between the incident beam and the light scattered by the nano-object. © 2011 IEEE.